First observation of correlated photons emitted by heavy highly charged ions in the process of radiative recombination - Tashenov, Stanislav; Banaś, Dariusz; Beier, Heinrich F.; Blumenhagen, Karl-Heinz; Brandau, Carsten; Gumberidze, Alexandre; Habermann, Tobias; Hagmann, Siegbert; Hillenbrand, Pierre-Michel; Kojouharov, Ivan; Kozhuharov, Christophor; Lestinsky, Michael; et al. (Journal of physics. Conference Series, 2014)
Dynamics of the electron spin in the Photoelectric Effect was studied in time-reversal via the process of Radiative Recombination. For this the photorecombination into an excited state of an ion and its subsequent radiative decay was observed. Pairs of correlated photons were detected in conicidence. Such an observation is the first of its kind for the initial ion as heavy as bare uranium.
XXVIII International Conference on Photonic, Electronic and Atomic Collisions (ICPEAC 2013)
Gesehen am 04.12.2020